MANAJEMEN PEMBINAAN KOMPETENSI GURU MADRASAH ALIYAH SWASTA ASSA’ADAH GUNUNG SUGIH LAMPUNG TENGAH - Umi Kulsum; Abdurrochman; Norma Fitria (UNISAN JURNAL, 2022)
The purpose of this study was to determine and analyze the development of the pedagogical competence of Madrasah Aliyah Assa’adah teachers at Gunung Sugih, Central Lampung, to find out and analyze the development of personality competencies of Madrasah Aliyah Assa’adah teachers at Gunung Sugih, Central Lampung, to identify and analyze the social competence development of teachers at madrasah Aliyah. knowing and analyzing the professional competence development of Madrasah Aliyah Assa’adah teachers in Gunung Sugih, Central Lampung. This research use desciptive qualitative approach. The data collection procedure used data collection methods of observation, interviews, and documentation studies. Data sources consist of Supervisors, Heads of Madrasahs, Leaders of Islamic Boarding Schools (kiyai) and Teachers. The data analysis technique is through data reduction steps, data presentation, conclusion drawing/verification. The data validity checking technique is based on four criteria, namely credibility, transferability, dependability, and confirmability.The results of the study indicate that the development of pedagogic competence, personality competence, social competence and professional competence is carried out through four things as follows: One, improving the academic qualifications of teachers, Two, coaching through a certification program Three coaching through integrated training, Four coaching through supervision The results of the fourth coaching Teacher competencies, namely pedagogic competence, personality competence, social competence and professional competence at the four Madrasah Aliyah have increased significantly through the development of skills and knowledge.